Docking Studies of Chlorogenic Acid against Aldose Redutcase by using Molgro Virtual Docker Software - Sadaf Naeem, Peter Hylands and David Barlow (Journal of Applied Pharmaceutical Science, 2013)
Docking studies of chlorogenic acid against aldose reductase, an enzyme involved in diabetic complications, have been performed, in order to evaluate the inhibitory effects of chlorogenic acid on this enzyme. The docking studies were performed using Molgro Virtual Docker (MVD) software. From the several available alternative methods to incorporate protein flexibility in docking studies, the use of multiple crystal structures with different bound ligands was applied here, thus, of the available crystal structures of the non- mutated aldose reductase enzyme from Homo sapiens, five were selected for the final docking studies. The docking results of chlorogenic acid with selected aldose reductase crystal structures shows that it forms hydrogen bonds with at least two out of three key active site residues (Tyr48, His110 and Trp111). It also form hydrogen bonds to other active site residues, in particular Thr113. The average MolDock score and the MolDock Re-rank score for cholorogenic acid are -119.34 Kcal/mol and -114.92 Kcal/mol respectively. The docking results show that chlorogenic acid fits well in the active site of aldose reductase and interact with the residues in the active site which are crucial for their biological activity, thus, it could a potent inhibitor of aldose reductase enzyme and thus be used for prevention/treatment of diabetic complications.
Keywords: Chlorogenic acid, aldose reductase, MVD, Diabetes.